Dengue fever as a reemerging disease in upper Egypt: Diagnosis, vector surveillance and genetic diversity using RT-LAMP assay - Mona Gaber; Alzahraa Abdelraouf Ahmad; Asmaa M. El-Kady; Mohammed Tolba; Yutaka Suzuki; Shereen M. Mohammed; Nahed Ahmed Elossily (PLoS ONE, 2022)
Background The recent increase in dengue virus (DENV) outbreaks and the absence of an effective vaccine have highlighted the importance of developing rapid and effective diagnostic surveillance tests and mosquito-based screening programs. To establish effective control measures for preventing future DENV transmission, the present study was established to identify the main mosquito vector involved in the dengue fever (DF) outbreak in Upper Egypt in 2016 and detect the diversity of dengue virus serotypes circulating in both humans and vectors. Methods We investigated the prevalence of DENV infection and circulating serotypes in the sera of 51 humans clinically suspected of DF and 1800 field-collected Aedes aegypti adult female mosquitoes grouped into 36 pooled samples. Both DENV non-structural protein (NS1) immunochromatographic strip assay and loop-mediated isothermal amplification (LAMP) were used for screening. Results Overall, the rate of DENV infection in both human sera and pooled mosquito homogenate was 33.3%, as revealed by rapid dipstick immunochromatographic analysis. However, higher detection rates were observed with RT-LAMP assay of 60.8% and 44.4% for humans and vector mosquitoes, respectively. DENV-1 was the most prevalent serotype in both populations. A combination of two, three, or even four circulating serotypes was found in 87.5% of total positive pooled mosquito samples and 83.87% of DENV-positive human sera. Conclusion The study reinforces the evidence of the reemergence of Aedes aegypti in Upper Egypt, inducing an outbreak of DENV. Mosquito-based surveillance of DENV infection is important to elucidate the viral activity rate and define serotype diversity to understand the virus dynamics in the reinfested area. Up to our knowledge, this is the first report of serotyping of DENV infection in an outbreak in Egypt using RT-LAMP assay.